2014
DOI: 10.1371/journal.pone.0102004
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Features and Survival Outcomes of Young Patients with Operable Colon Cancer: Are They Homogeneous?

Abstract: ObjectiveTo compare the pathological features and survival outcomes at different age subgroups of young patients with colon cancer.MethodsUsing Surveillance, Epidemiology, and End Results (SEER) population-based data, we identified 2,861 young patients with colon cancer diagnosed between 1988 and 2005 treated with surgery. Patients were divided into four groups: group 1 (below 25 years), group 2 (26–30 years), group 3 (31–35 years) and group 4 (36–40 years). Five-year cancer specific survival data were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…This study has several limitations. First, the SEER database does not include information of therapeutic options such as detailed information of chemotherapy, targeted therapy, immunotherapy, recurrence and metastasis, which may also impact patients’ prognosis [ 35 ]. Second, the SEER database is lack of detailed description of the organ metastasis (liver, lung, bone or brain).…”
Section: Discussionmentioning
confidence: 99%
“…This study has several limitations. First, the SEER database does not include information of therapeutic options such as detailed information of chemotherapy, targeted therapy, immunotherapy, recurrence and metastasis, which may also impact patients’ prognosis [ 35 ]. Second, the SEER database is lack of detailed description of the organ metastasis (liver, lung, bone or brain).…”
Section: Discussionmentioning
confidence: 99%
“…Higher frequencies of mucinous adenocarcinoma and signet ring cell carcinoma (SRCC) have been seen in several studies 2 5 10–13. Discrepancies exist in the prognoses of patients with EOCRC.…”
Section: Introductionmentioning
confidence: 94%
“…Discrepancies exist in the prognoses of patients with EOCRC. Some studies have suggested a poorer prognosis in patients with EOCRC,2 4 14 whereas others have reported that their prognosis is similar to, or even more favourable than, that of patients with general CRC because they usually have a better performance status 1 3 6 11–13 15 16…”
Section: Introductionmentioning
confidence: 99%
“…When considering early onset CRC, the age definition of the group referred to as "adolescent and young adults" (AYA) is still debated [4]. Age cutoffs vary widely among published studies; some authors recommend an upper limit of 50 years of age, based on historically recommended CRC screening guidelines in the average-risk population, whereas others select patients below the age of 40 years based on physiological and pathological variables [5][6][7]. In addition, data on outcomes of younger patients with CRC are inconsistent, with reports showing either a worse or a better outcome when compared with their older counterparts [5][6][7].…”
Section: Introductionmentioning
confidence: 99%